Inflammatory Cytokines in Diabetic Kidney Disease: Pathophysiologic and Therapeutic Implications - Donate-Correa, Javier; Ferri, Carla M.; Sánchez-Quintana, Fátima; Pérez-Castro, Atteneri; González-Luis, Ainhoa; Martín-Núñez, Ernesto; Mora-Fernández, Carmen; Navarro-González, Juan F. (Frontiers in Medicine, 2021)
Diabetic kidney disease (DKD) constitutes the first cause of end-stage renal disease and is a main factor contributing to cardiovascular morbidity and mortality in patients with diabetes mellitus. Strategies employed to delay the progression of this pathology are focused on the control of traditional risk factors, such as hyperglycemia and elevated blood pressure. Although the intimate mechanisms involved in the onset and progression of DKD remain incompletely understood, inflammation is currently recognized as one of the main processes underlying this complication. Understanding the cascade of signals and mechanisms that trigger the appearing of a harmful inflammatory response in the diabetic patient is crucial in the identification of new targets and in the development of innovative therapeutic strategies. In this review, we focus on the pathogenic mechanisms of the inflammatory cytokines involved in DKD, and discuss the utility of new strategies that target inflammation.